The father's perception about home birth and birth of the child with obstetric nurses - Moura, Reinaldo dos Santos (2022)
Objective: To describe the father's perception of home birth and the birth of his child assisted by a group of obstetric nurses. Methodology: Study with a qualitative, descriptive and exploratory approach through oral life histories. Carried out with parents who experienced home births with a group of obstetric nurses, through interviews with a semi-structured script and content analysis by thematic category. Results: The narrators were characterized with important variables for understanding and the oral life stories were synthesized in 03 thematic categories, namely: I – The creation of a bond between the obstetrician nurse and the father as a positive factor for the phenomenon; II – Experiences and feelings; and III – The strength of his wife as an admirable factor. Final Considerations: It was observed that being a father during home birth with the group of obstetric nurses had the externalization of feelings such as tension, fear, joys and, mainly, the understanding of marital strengthening with the resignification of pregnancy and childbirth safely.